2010
DOI: 10.1119/1.3481701
|View full text |Cite|
|
Sign up to set email alerts
|

Smooth double barriers in quantum mechanics

Abstract: Quantum mechanical tunneling across smooth double barrier potentials modeled using Gaussian functions, is analyzed numerically and by using the WKB approximation. The transmission probability, resonances as a function of incident particle energy, and their dependence on the barrier parameters are obtained for various cases. We also discuss the tunneling time, for which we obtain generalizations of the known results for rectangular barriers.Comment: 23 pages, 8 figures, a slightly reduced version to appear in A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Recently, a revival of interest in the paradox is arisen [15][16][17] due to the research in tunneling through double barrier. [18][19][20] The simplest case is the one-dimensional rectangular double barrier (RDB), and it has been found that even in the free propagation region between two barriers, the velocity of the tunneling particle can still be far larger than its typical value in free space.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a revival of interest in the paradox is arisen [15][16][17] due to the research in tunneling through double barrier. [18][19][20] The simplest case is the one-dimensional rectangular double barrier (RDB), and it has been found that even in the free propagation region between two barriers, the velocity of the tunneling particle can still be far larger than its typical value in free space.…”
Section: Introductionmentioning
confidence: 99%
“…Model potentials of a double well are indeed treated in most textbooks, and even in many pedagogical-style articles. [7][8][9][10][11][12] The treatment of a double well potential in textbooks will vary from qualitative discussion (see, for example, Problem 2.47 in Griffiths, 1 ) to an analytical solution (for example, Section 8.5 in Merzbacher, 13 where, however, advanced mathematical steps are required). More often, the Wentzel-Kramers-Brillouin (WKB) approximation is used (see, for example, Problem 8.15 in Griffiths, 1 and Problem 7.2, and 8.10 in Merzbacher.…”
Section: Introductionmentioning
confidence: 99%
“…First, they provide a new subwavelength potential landscape. Quasi-bound states and resonant tunnelings of multibarrier potentials can be studied using Wentzel-Kramers-Brillouin (WKB) approximation [47,48]. The potentials can also form multi-barrier lattices since f (x) has a period of λ, thus they are useful for the study of band structures, and even trapping atoms through the quasi-bound states.…”
Section: Additional Tunabilitymentioning
confidence: 99%